2017
DOI: 10.1186/s11782-017-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion and emotional demands in China: a large-scale investigation across occupations

Abstract: As the Chinese economy moves toward a market-based model, employees are likely to face more emotional demands and exhaustion at work. However, there are some unique aspects to the emotional demands of work in the Chinese cultural context. We investigate emotional demands and exhaustion in China with a large-scale sample across the six major occupations identified by the Holland classification system. Results show that incumbents of social and enterprising jobs face higher emotional demands. Unexpectedly, exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
2
0
1
Order By: Relevance
“…This research suggests that, when an organization reduced the negative impact of emotional exhaustion, it needs to seriously consider more about the emotional demand creating factors and by controlling these factors, employees can be able to work with emotional satisfaction. This finding of the study consistent with the findings of previous studies, such as emotional demand positively related with emotional exhaustion (Brotheridge & Grandey, 2002;Tuxford & Brandley, 2014;Peng, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This research suggests that, when an organization reduced the negative impact of emotional exhaustion, it needs to seriously consider more about the emotional demand creating factors and by controlling these factors, employees can be able to work with emotional satisfaction. This finding of the study consistent with the findings of previous studies, such as emotional demand positively related with emotional exhaustion (Brotheridge & Grandey, 2002;Tuxford & Brandley, 2014;Peng, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…For example, Garcia et al [ 11 ] and Schyns et al [ 12 ] explored the positive relationship between perceived task demand and job satisfaction. Considering the transformation of the economic system and the high-speed development of China, Chinese employees are more likely than ever to face increased task demands [ 13 , 14 , 15 ]. In particular, after the outbreak of the COVID-19 pandemic, nearly 74% of female Chinese employees have reported that their task demands have increased [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…La creciente atención que ha recibido el trabajo emocional durante las últimas décadas, no solo se relaciona con su alta prevalencia asociada al crecimiento del rubro de servicios, sino también a las consecuencias que este ha evidenciado tener para la salud y bienestar de trabajadores (Framke et al, 2019;Hülsheger y Schewe, 2011;Peng, 2017;Zapf et al, 2001). Es una evidencia metaanalítica que aborda el trabajo emocional como un proceso intrapsíquico, que muestra que la estrategia superficial tiene efectos negativos para los trabajadores, en tanto se asocia a mayores niveles de estrés, mayor burnout (Grandey, 2003) y menor satisfacción laboral (Hülsheger y Schewe, 2011;Kammeyer-Mueller et al, 2013).…”
Section: Introducción El Trabajo Emocionalunclassified